2013
DOI: 10.1021/ja4015452
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hydrophobic Interactions in the Encounter Complex Formation of the Plastocyanin and Cytochrome f Complex Revealed by Paramagnetic NMR Spectroscopy

Abstract: Protein complex formation is thought to be at least a two-step process, in which the active complex is preceded by the formation of an encounter complex. The interactions in the encounter complex are usually dominated by electrostatic forces, whereas the active complex is also stabilized by noncovalent short-range forces. Here, the complex of cytochrome f and plastocyanin, electron-transfer proteins involved in photosynthesis, was studied using paramagnetic relaxation NMR spectroscopy. Spin labels were attache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 63 publications
3
58
0
Order By: Relevance
“…In the encounter complex, the proteins assume multiple other orientations, often in equilibrium with the major stereospecific state. In low-affinity complexes with dissociation constant (K d ) values > 10 μM, the encounter complex can represent a sizeable fraction, and in some cases, a well-defined, stereospecific complex may even be absent (10)(11)(12)(13)(14)(15). The presence of encounter states may be a consequence of the chemical nature of proteins.…”
mentioning
confidence: 99%
“…In the encounter complex, the proteins assume multiple other orientations, often in equilibrium with the major stereospecific state. In low-affinity complexes with dissociation constant (K d ) values > 10 μM, the encounter complex can represent a sizeable fraction, and in some cases, a well-defined, stereospecific complex may even be absent (10)(11)(12)(13)(14)(15). The presence of encounter states may be a consequence of the chemical nature of proteins.…”
mentioning
confidence: 99%
“…Minimal ensembles reported to represent the loosely bound, transient encounter complexes observed by paramagnetic NMR in other protein associations have up to 7-10 members (38,58,68). Remote binding of the collagen V miniprotein to the ␤-sheet, active site, and possibly elsewhere had been suggested by its protection of these surfaces of MMP-12 cat from solvent PREs introduced by a Gd⅐EDTA probe (28).…”
Section: Encounter Complexes and Implicationsmentioning
confidence: 99%
“…Encounter complexes have been hypothesized to speed up the process of molecular recognition by reducing the search from three to two dimensions through the formation of weak electrostatic (58) or hydrophobic (38) interactions. The hydrophobic and conserved nature of the large serpentine path filled by transient complexes reinforces its potential as harboring "loading complexes", i.e.…”
Section: Encounter Complexes and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[35] Visualization of the encounter complex of Cyt c and Cyt c peroxidase was successfully achieved using PRE data and rigid-body MC simulations. [36] The results showed that formation of this encounter complex was driven by charge-charge interactions.…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%